Hippo pathway controls cell adhesion and context‐dependent cell competition to influence skin engraftment efficiency. Issue 4 (14th January 2019) - Nishio, Miki; Miyachi, Yousuke; Otani, Junji; Tane, Shoji; Omori, Hirofumi; Ueda, Fumihito; Togashi, Hideru; Sasaki, Takehiko; Mak, Tak Wah; Nakao, Kazuwa; Fujita, Yasuyuki; Nishina, Hiroshi; et al.
ABSTRACT: Cell competition is involved in mammalian embryogenesis and tumor elimination and progression. It was previously shown that, whereas NIH3T3 mouse fibroblasts expressing high levels of the yes‐associated protein 1(YAP1) target TEA domain family (TEAD) transcription factors become "winners" in cell competitions, Madin‐Darby canine kidney cells expressing activated YAP1 become "losers" and are eliminated from culture monolayers. Thus, YAPl's role in cell competitions is clearly context dependent. Here, we show that keratinocytes overexpressing a constitutively activated YAP1 mutant lose in in vitro competitions with control cells conducted in standard tissue culture dishes and undergo apical extrusion. Similarly, cells in which endogenous YAP1 is activated by NF2 knockdown become losers. The YAP1‐overexpressing cells exhibit a decrease in cell‐matrix adhesion because of defective expression of adhesion molecules such as fibronectin‐1. Cell adhesion‐mediated proliferation is also impaired. However, because of intrinsic factors, YAP1‐expressing cells proliferate faster than control cells when cocultured in dishes impeding cell adhesion. In vivo, Mob1a / b ‐deficient (YAP1‐activated) epidermis, which shows decreased expression of type XVII collagen, cannot be engrafted successfully onto donor mice. YAP1‐activated skin grafts shrink away from surrounding control skin, and the epidermis peels off the basement membrane. Our data show that YAP1 activation controls cell competition in part by decreasing cell adhesion.—Nishio, M., Miyachi, Y., Otani, J., Tane, S., Omori, H., Ueda, F., Togashi, H., Sasaki, T., Mak, T. W., Nakao, K., Fujita, Y., Nishina, H., Maehama, T., Suzuki, A. Hippo pathway controls cell adhesion and context‐dependent cell competition to influence skin engraftment efficiency. FASEB J. 33, 5548–5560 (2019). www.fasebj.org